TOMCAT (TAKE YOUR COMFORTABLE WAISTCOAT) - Aprilia, Entri; Muhtasir, Fajar Farhan; Suparno, Lenny Komariyah; Pratiwi, Tiara Dwinda (Program Kreativitas Mahasiswa - Kewirausahaan, 2013)
At this time, people prefer to use motor bikes compared with other transportation modes. Because they think a motorcycle is much more economical and efficient. However this has an impact on our health. Too often exposed to high winds without adequate protected jacket will easily make the body become unfit. Proposed student creativity program contains an attempt to reduce these risks, by making herbal scented warmers vest therapy. This aims to protect the body from wind with the help of herbal ingredients and heating elements. In addition, this vest can also be used for medical therapy.Keyword : vest, warm, herbal, aroma therapy